Fashion Sebagai Identitas Pada Komunitas Punk di Semarang - Rayhan Ferdiyanto, Rakha; Budi Lestari, Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Fashion is one of the ways a person communicates, where fashion can reflect the wearer, however, this is the case with punk followers. Punk uses fashion as their way of communicating messages to the public. As a counter-culture or counter-culture to the dominant culture, punk fights against all establishment shown by the dominant culture through a